Does the dual VET bring curriculum improvements? A normative analysis in the Spanish contex - Chisvert-Tarazona, Maria José [Verfasser]; Vila-Vázquez, Javier [Verfasser]; Ros-Garrido, Alicia [Verfasser]; Palomares-Montero, Davinia [Verfasser] (My University, 2021)
"The recent introduction of dual vocational training (DVT) in Spain attempts to implement a new model of vocational training by replicating German DVT. The aim of this change in vocational education, as stated by the Spanish regulation, is to improve student learning and increase employability. The export of a model that has been successful in one country to another country does not seem to work properly in Spain because it is a country that does not have a tradition of this kind of training and its economic and social systems differ from those of the originating country. To measure the adequacy of a system, one parameter that may be used is the analysis of curricular improvements, since the curricular design seeks to respond to the needs of the labor market by adapting to the needs of companies. In Spain, the implementation of the DVT does not seem to guarantee the acquisition of new competencies but rather guarantees a null curriculum, that is, thosec ompetenciesth at aren ot taughtb ut deservet o be taught." (Author's abstract ; BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; S 1.3.1 Ausbildung im Dualen System; L 1 Curricula & Lehrpläne; 370; Spanien; Bildungstransfer; Duales System; Curriculum